Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.1 - The Algebra of Functions - Exercise Set - Page 842: 9


$(f\circ g)(2)=42$

Work Step by Step

$f(x)=x^{2}-6x+2;$ $g(x)=-2x$ $(f\circ g)(2)$ First, find $g(2)$ by substituting $x$ with $2$ in $g(x)$: $g(2)=-2(2)=-4$ Now, find $(f\circ g)(2)$ by substituting $x$ with $-4$ in $f(x)$: $(f\circ g)(2)=f(g(2))=f(-4)=(-4)^{2}-6(-4)+2=...$ $...=16+24+2=42$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.